Intestinal Parasitic Infections among HIV-Infected Patients on Antiretroviral Therapy Attending Debretabor General Hospital, Northern Ethiopia: A Cross-Sectional Study - Alemayehu, Ermias (HIV AIDS (Auckl), 2020)
BACKGROUND: Parasitic infections are known causes of morbidity among HIV-infected patients with low CD4(+) counts who are on antiretroviral therapy (ART), mainly as a result of immuno suppression. This study aimed to assess the extent of intestinal parasitic infection and related risk factors among HIV-infected patients attending ART clinic at Debretabor General Hospital, Northern Ethiopia. METHODS: A health facility–based cross-sectional study was conducted on 383 HIV-infected patients attending the ART clinic of Debretabor General Hospital, northern Ethiopia from December 2018 to March 2019. An interview-based structured questionnaire was used to gather sociodemographic and risk-factor data. About 5 g fresh stool and 4 mL venous blood were collected from each patient, then transported and tested in accordance with laboratory-standard operating procedures. Data obtained were entered into SPSS version 22.0 and analyzed. P<0.05 with 95% CI was considered statistically significant. RESULTS: The overall prevalence of intestinal parasites was 25.3%, with 18% and 23.8% by direct wet-mount and formol ether–concentration technique, respectively. Eight (2.1%) patients were infected by multiple parasites using the concentration technique. Ascaris lumbricoides was the most frequently identified parasite (n=23, 25.3%). Parasitic infection was significantly higher among illiterates (P=0.011), patients with CD4 count <200 cells/mm(3) (P<0.001), and those who did not have a toilet in their home (P=0.049) than their counterparts. CONCLUSION: Relatively higher prevalence of intestinal parasitic infection was found among HIV/AIDS patients. The distribution of intestinal parasites was greatly affected by illiteracy, reduced CD4(+) counts, and absence of a toilet. Therefore, HIV/AIDS patients with low CD4(+) counts should be diagnosed consistently for intestinal parasites with routine stool examinations, and awareness creation should be advocated to be included as an essential component of ART-monitoring strategies for improved patient care.